2017
DOI: 10.1111/jre.12512
|View full text |Cite
|
Sign up to set email alerts
|

Temporal expression of interleukin‐22, interleukin‐22 receptor 1 and interleukin‐22‐binding protein during experimental periodontitis in rats

Abstract: This study shows the expression and localization of IL-22, IL-22R1 and IL-22BP, as well as the relevant histopathological alterations during the development of experimental periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Pathologically, Th22 lymphocytes have been implicated in the immunopathogenesis of several inflammatory and autoimmune diseases . During experimental periodontitis, abundant IL‐22 + cells were observed in periodontal lesions . Similarly, a greater number of CD4 + IL‐22 + AhR + T lymphocytes was detected in periodontal tissues obtained from periodontitis patients compared with healthy individuals .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathologically, Th22 lymphocytes have been implicated in the immunopathogenesis of several inflammatory and autoimmune diseases . During experimental periodontitis, abundant IL‐22 + cells were observed in periodontal lesions . Similarly, a greater number of CD4 + IL‐22 + AhR + T lymphocytes was detected in periodontal tissues obtained from periodontitis patients compared with healthy individuals .…”
Section: Discussionmentioning
confidence: 99%
“…Using an animal model of periodontitis, IL‐22 + cells were clearly observed both in the gingival epithelium and in the nearby lamina propria in experimental periodontal lesions, and when human T lymphocytes were stimulated in vitro with Aggregatibacter actinomycetemcomitans , these cells showed higher expression levels of IL‐22 and AhR than non‐stimulated cells . In this context, a greater number of CD4 + IL‐22 + AhR + T lymphocytes was detected in periodontal tissues obtained from periodontitis patients compared with healthy individuals .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Periodontitis, caused by altered host-biofilm interactions in the gingival crevice, is the most common infectious disease and leads to progressive alveolar bone destruction and eventual tooth loss in humans (Barbato et al, 2015;Papapanou & Susin, 2017). Therefore, periodontal bone resorption is closely linked to the host immune response to a microbial challenge (Díaz-Zúñiga et al, 2017;Ghighi et al, 2018;Hienz, Paliwal, & Ivanovski, 2015;Pan et al, 2018;Takayanagi, 2005). During such pathological cascades, many immune cells polarize toward proinflammatory responses; for example, we previously reported increased levels of M1 phenotypes of macrophages in inflammatory gingival tissues .…”
Section: Introductionmentioning
confidence: 99%
“…CRSwNP (Pan et al, 2018;Khalmuratova et al, 2020). Only one study has shown that CRSwNP can impair the olfactorial signaling pathway and neuroactive ligand receptor pathway by affecting the expression of "olfactorial receptor activity" and "channel activity" genes (Xiong et al, 2020).…”
Section: Data Availability Statementmentioning
confidence: 99%